Electrochemical deconstruction of waste polyvinylidene chloride (PVDC) to value-added products in batch and flow - Mishra, Subhadip; Kar, Sourav; Rangappa, Raghavendrakumar; Patil, Prashant; Kadam, Vijay; Chikkali, Samir H.; Samanta, Ramesh C. (Chemistry-A European Journal, 2025)
Chlorinated polymers have made enormous contributions to materials science and are commercially produced on a large scale. These chlorinated polymers could be recycled as chlorine sources to efficiently produce valuable chlorinated compounds owing to their facile release of HCl. Although the thermal stability of PVDC is low compared to PVC, this can be advantageous in terms of easy and fast dehydrochlorination. Herein, we report an efficient electrochemical chlorination using poly(vinylidene chloride) (PVDC) as a chlorine source that works in an undivided cell and applies to a good number of examples. This method works on commodity polymers such as waste PVDC-PVC pharma blister film, PVDC-PO multilayer food packaging, and compression molded sheets of Ixan PVDC (with heat stabilizer) with similar efficiency. Furthermore, this method also provides the dechlorination of PVDC up to 98 %, leading to unsaturated dechlorinated material. Converting PVDC into more stable unsaturated compounds, the release of harmful chlorine-containing gases during incineration can be minimized. Additionally, this method is not only restricted to batch processes but an electroflow process for PVDC dechlorination and electrosynthesis has also been demonstrated.
Keywords: chlorination; Electrochemical recycling; Electroflow-synthesis; Graphitic material; Polyvinylidene chloride